Configurations textuelles de l'intime aux XIIe et XIIIe siècles. Luminița Diaconu - Marfouq, Assia (Estudios Románicos, 2026)
<pre id="tw-target-text" class="tw-data-text tw-text-large tw-ta" dir="ltr" style="text-align: left;" data-placeholder="Traducción" data-ved="2ahUKEwj-ga_Mt76OAxXLK_sDHTFYJDwQ3ewLegQIDRAV" aria-label="Texto traducido: Published in 2024 by L’Harmattan, in the Literary Criticism collection edited by Jérôme Martin, Luminița Diaconu’s Textual Configurations of the Intimate in the 12th and 13th Centuries is an erudite study that examines the textual forms of intimacy in the Central Middle Ages (12th-13th centuries), from a philological, anthropological, and hermeneutic perspective. This work is organized around a dual ambition: first, to question the very existence of a medieval intimate, insofar as modern concepts of individuality, interiority, or private life seem, at first glance, incompatible with a deeply communitarian, hierarchical medieval society structured by religious and social norms. Then, analyze the “textual configurations” of this intimacy in courtly and religious literature, through a rich and varied corpus with the aim of highlighting spaces, narrative structures and enunciative devices which make a nascent interiority thinkable, torn between personal desire and collective norms.">Published in 2024 by L’Harmattan, in the Literary Criticism collection edited by Jérôme Martin, Luminița Diaconu’s Textual Configurations of the Intimate in the 12th and 13th Centuries is an erudite study that examines the textual forms of intimacy in the Central Middle Ages (12th-13th centuries), from a philological, anthropological, and hermeneutic perspective. This work is organized around a dual ambition: first, to question the very existence of a medieval intimate, insofar as modern concepts of individuality, interiority, or private life seem, at first glance, incompatible with a deeply communitarian, hierarchical medieval society structured by religious and social norms. Then, analyze the “textual configurations” of this intimacy in courtly and religious literature, through a rich and varied corpus with the aim of highlighting spaces, narrative structures and enunciative devices which make a nascent interiority thinkable, torn between personal desire and collective norms.